Template-induced Bi2O2CO3 microstructure self-assembled by nanosheets with exposed 001 facets. (6th June 2018) - Cheng, Lijun; Hu, Xumin; Hao, Liang
Abstract: Bi2 O2 CO3 microstructures self-assembled by nanosheets with exposed 001 facets were synthesized via a facile cetyltrimethyl ammonium bromide (CTAB)-assisted hydrothermal process. X-ray diffraction (XRD), Scanning electron microscopy (SEM), Transmission electron microscopy (TEM), Brunauer–Emmett–Teller (BET) surface area analysis, X-ray photoelectron spectroscopy (XPS), UV–vis diffuse reflectance spectroscopy (UV–vis DRS) and Photoluminescence (PL) spectra were used to characterize the as-prepared samples. Compared to Bi2 O2 CO3 microstructure obtained without any template, the template-assisted Bi2 O2 CO3 microstructure demonstrated enhanced photocatalytic activity, which mainly resulted from exposure of 001 facets, narrower band gap and less recombination of charge carriers. When the addition amount of CTAB was 0.6 g, the exposure percentage of 001 facets was largest, the band gap smallest and charge carrier separation most effective, giving rise to highest photoreactivity for RhB degradation. Approximately 97.67% of RhB degradation efficiency was achieved within 45 min. Moreover, holes were proved to be the dominant active species in the photocatalytic process.